Traditional and Complementary Medicine in Tanzania: Regulation Awareness, Adherence and Challenges - Phares Mujinja; Happiness Saronga (International Journal of Health Policy and Management, 2022)
Background  The demand for and use of Traditional and Complementary Medicine (T&CM) has recently increased worldwide drawing a public health attention including malpractice, which puts the health of its clients at risk. Despite efforts made by Tanzania to integrate T&CM in the health system to protect the clients, regulating the subsector has remained a challenge due to lack of information and operational factors facing the regulatory frameworks in Tanzania. The aim of this study was to determine the extent of imperfect information, regulation adherence and challenges among T&CM practitioners and regulators in Tanzania. Methods  In-depth interviews were carried out with T&CM practitioners in Dar es Salaam Region in Tanzania, and officials from the Ministry of Health and the study municipals. Purposive and snowballing approaches were used to select study participants. Thematic data analysis was done with the help of NVIVO.Results  Awareness of regulations and tools used for regulating the T&CM operations among practitioners was generally very low. There was fragmentation of knowledge on what they were practicing as well as on awareness of the regulations, and what is regulated. Practitioners argued that they cannot be controlled by conventional medical trained personnel. Regulators at municipal level reported to have had no knowledge, interest, and time to work on T&CM. Lack of adequately trained and qualified manpower, lack of financial resources, poor transport and other infrastructure at the municipal regulatory units aggravated non-adherence to regulations, and therefore rendered ineffectiveness to the regulatory framework. Conclusion  Existence of imperfect information on T&CM among regulators and practitioners affect effectiveness of T&CM regulatory process. Awareness of regulations among practitioners, presence of knowledgeable regulators, as well as capacity would facilitate adherence to regulations.